Implementation of Village Fund Allocation Utilization Program in Improving Community Empowerment (Case Study in Baribis Village of Cigasong District of Majalengka Regency, Indonesia) - Dody Kusmayadi (Budapest International Research and Critics University, 2022)
This research is an effort to explain the implementation of the policy of using village funds sourced from village funds, allocation of village funds, and government assistance. The village fund is expected to positively impact village development or community welfare efforts in Baribis Village. However, village funds are still not enough to create welfare for the community. This study aims to get an overview of the implementation of the village funds utilization policy in the Baribis Village government. In addition, to find out what steps the Baribis Village Government takes to utilize village funds. The method used in this research is a qualitative research method based on its object using a normative approach. The collection techniques used are primary data obtained from interviews and secondary data obtained from village documents, books, journals, scientific papers. The study results showed that the implementation of village funds in the Village Government of Baribis Cigasong District of Majalengka Regency was carried out through the implementation and evaluation stages and good management carried out by the Baribis Village Government.